Age and fashion: A study of ambiguous status representation in granny chic. Issue 1 (1st October 2013) - Mackinney-Valentin, Maria
The research objective with this article is to examine the role of age in granny chic. Granny chic is understood as a contemporary fashion phenomenon characterized as the celebration by younger consumers of elements that may generally be considered to belong to the realm of older women, such as grey hair, orthopaedic shoes, craft and old clothes. The article challenges the binary construction of 'young' versus 'old', which is based on a biogerontological model of aging as decline (Kriebernegg and Maierhofer 2013). It explores whether the rise of granny chic since the millennium suggests a move towards an 'age-irrelevant society' (Cole 1992: 241) with a rise in tolerance for age diversity. To that end, it draws on age and ageing theory to question whether the nature of age in 'granny chic' is less about chronological age and more about old age as a symbolic tool for negotiating social status among younger consumers. Examples are drawn from the fashion industry with special attention to fashion campaigns, fashion spreads in magazines and runway shows. In addition, examples of granny chic in food and leisure are referenced. This article is not about older women per se, but about the social paradox of celebrating the old, imperfect and out-dated in an age focused on newness and perfection. The study uses a narrative method for the study of 'granny chic' as a fashion phenomenon. It analyses the representation in images and texts in mainly American and British newspapers, magazines and blogs – from 2010 to 2012.